A life cycle assessment framework for large-scale changes in material circularity. (November 2021) - Andreasi Bassi, Susanna; Tonini, Davide; Ekvall, Tomas; Astrup, Thomas F.
Highlights: A LCA framework to address large-scale changes due to circular economy is presented. The mathematical formulation of the environmental consequences is illustrated. Supply and use of recycled material should be jointly assessed. Non-linear market responses and dynamic modelling is suggested. Abstract: Increasing material circularity is high on the agenda of the European Union in order to decouple environmental impacts and economic growth. While life cycle assessment (LCA) is useful for quantifying the associated environmental impacts, consistent LCA modeling of the large-scale changes arising from policy targets addressing material circularity (i.e., recycled content and recycling rate) is challenging. In response to this, we propose an assessment framework addressing key steps in LCA, namely, goal definition, functional unit, baseline versus alternative scenario definition, and modeling of system responses. Regulatory and economic aspects (e.g., trends in consumption patterns, market responses, market saturation, and legislative side-policies affecting waste management) are emphasized as critical for the identification of potential system responses and for supporting regulatory interventions required to reach the intended environmental benefits. The framework is recommended for LCA studies focusing on system-wide consequences where allocation between product life cycles is not relevant; however, the framework can be adapted to include allocation. The application of the framework was illustrated by an example of implementing a policy target for 2025 of 70% recycled content in PET trays in EU27+1. It was demonstrated that neglecting large-scale market responses and saturation lead to an overestimation of the environmental benefits from the policy target and that supplementary initiatives are required to achieve the full benefits at system level.